2019
DOI: 10.5001/omj.2019.95
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Knowledge, Attitudes, and Implementation of Evidence-based Practice in Oman: A Multi-institutional, Cross-sectional Study

Abstract: ObjectivesLittle attention has been paid to the study of evidence-based practice (EBP) among nurses in Oman. Our aim was to explore knowledge, practice, and attitudes towards EBP among nurses working in Oman.MethodsThis multi-institutional cross-sectional study utilized the self-reported EBP Questionnaire with a random sample of 262 nurses working in three different health care settings in Al Dakhliyah governorate, Oman (local hospitals, primary health centers and polyclinics, and schools).ResultsA total of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
31
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 17 publications
(48 reference statements)
9
31
1
1
Order By: Relevance
“…The current study demonstrated that the majority of the studied nurses had a negative attitude regarding EBP. These finding is in contrast with Mohsen et al [28], Padmanabhanunni [29], Al-Maskari et al [30], and Al-Busaidi et al [31] reported that all nurses have a positive attitude toward EBP.…”
Section: Nurses' Altitude Toward Evidence Basedmentioning
confidence: 60%
See 1 more Smart Citation
“…The current study demonstrated that the majority of the studied nurses had a negative attitude regarding EBP. These finding is in contrast with Mohsen et al [28], Padmanabhanunni [29], Al-Maskari et al [30], and Al-Busaidi et al [31] reported that all nurses have a positive attitude toward EBP.…”
Section: Nurses' Altitude Toward Evidence Basedmentioning
confidence: 60%
“…The present study Findings revealed that no statistical significant difference was found between nurses' level of education and their attitude toward EBP. In contrast AbuRuz et al [33], Al-Maskari [31], and Ammouri et al [35] reported that increased education levels had a positive effect on overall attitudes towards EBP.…”
Section: Nurses' Altitude Toward Evidence Basedmentioning
confidence: 92%
“…The level of nurses' confidence in the importance of evidence-based practice becomes a positive value in implementing, this from several studies conducted in various countries such as Korea, China, Greece, Iraq, Oman, and Singapore (Majid et al , 2011;Khammarnia et al, 2015;Patelarou et al, 2016;Al-Busaidi et al, 2019;Chen et al, 2019;Yoo et al, 2019) suggested that nurses' confidence in EBP was quite high. In this series of studies, it clearly showed the nurse population alone so that data showing nurses' belief in EBP in high significant values but research conducted in Taiwan by looking at EBP confidence comparisons on the multi profession.…”
Section: Implementation Of Ebp Nurses On An Individual Levelmentioning
confidence: 99%
“…This conformity with the findings ( Yoo and Linger) that nurses with a bachelor's degree have significance with vocational nurses and nurses who have taken EBP classes are also more essential than those who do not. Hence, other factors that influence knowledge related to demographics are also sourced in the length of work (Al-Busaidi et al, 2019) so that in studies that use the following two simultaneously variables use filed multilevel regression submission, changed with more pure variables. In research conducted (Pittman et al, 2019).…”
Section: Implementation Of Ebp Nurses On An Individual Levelmentioning
confidence: 99%
“…Despite the challenges faced by nurses and doctors, their EBP perception was positive and the factors influencing their EBP were recognized. Nurses have positive EBP perception, especially their attitude in most studies (AbuRuz et al, 2017;Al-Busaidi et al, 2019;Alqahtani et al, 2020;Kalhor et al, 2017;Naderkhah et al, 2016;Novrianda & Hermalinda, 2019;Zhou et al, 2016). Some of these studies reported various relationships or influencing factors such as age, gender, education, working experience, and role.…”
Section: Introductionmentioning
confidence: 99%